Under pressure: an ocular complication of oral corticosteroid therapy. (11th September 2012) - Fitzgerald, Lucy Anne; Dudley, Jan; Inward, Carol; Tizard, Jane
Abstract : We describe the case of a patient with steroid sensitive nephrotic syndrome who is admitted with headaches, eye pain and reduced visual acuity. Despite thorough investigation no cause for the pain is identified. On a subsequent admission for recurrence of her symptoms her intraocular pressures are measured, which are markedly raised. Immediate medical treatment, as well as prompt weaning of her steroid therapy avoided the need for trabeculectomy surgery. We review this case and the literature surrounding this condition in children.